Pemakaian Media Pembelajaran Untuk Memperbaiki Kualitas Pendidikan Agama Islam di SMA Muhammadiyah 2 Ngawi - Bermi, Wibawati (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2022)
Efforts to achieve quality education, in providing learning materials teachers repeatedly encounter difficulties. In efforts to improve the teaching and learning process, the use of media is an appropriate alternative. One of the uses of media in an effort to help teachers convey learning is by utilizing media, because the media can not only help teachers but can also help students in the teaching and learning process. It can be seen that to overcome the problems that occur in the learning process the teacher can take advantage of learning media that are around the school and outside the school. This study aims to find out (a) the learning media used to improve the quality of Islamic Religious Education at Muhammadiyah 2 Ngawi High School (b) The use of media in learning can improve the quality of Islamic Religious Education at Muhammadiyah 2 Ngawi High School. This type of research is descriptive qualitative which aims to be able to clearly describe that instructional media can improve the quality of Islamic Religious Education at SMA Muhammadiyah 2 Ngawi. The author conducted this research at Muhammadiyah 2 Ngawi High School in class 11 Science from November 1 to December 31 2022. The conclusions from this study stated that the use of media such as prayer rooms, textbooks, infocus, student worksheets used in the learning process in high school Muhammadiyah 2 Ngawi can stimulate and improve the quality of Islamic Religious Education at SMA 2 Muhammadiyah Ngawi. Keywords: Learning Media, Quality, Islamic Religious Education